PENERAPAN PEMBELAJARAN TATA BAHASA ARAB MELALUI MUSIK GERAK DAN LAGU DI MAN 1 GARUT - Ujang Deden Nurul Hakim (Jurnal Pendidikan UNIGA, 2018)
Vocabulary and grammatical grammar is one of the important components of language for the occurrence of language communication between each other. Without much vocabulary, and knowing the grammar framework a person can not understand what others are saying and there will be gaps in communication. Learning foreign language vocabulary including Arabic is often a common problem for students. even they often conclude that learning arabic language is difficult, complicated because the various isthilah grammar so much, especially for those who do not learn in boarding school. The use of appropriate methods is needed by teachers in creating an interesting atmosphere in teaching and learning activities for young learners. Music and songs are one of the methods that teachers can use to teach students. This is in accordance with the characteristics of learners who are relatively still young age. Using music and songs as a supporting medium in the teaching and learning process is one way that may have a significant effect for students on their vocational achievement.